Faktor-Faktor Pendorong dan Penghambat Adopsi Teknologi Informasi untuk Pengembangan e-Tourism - Wheny Khristianto (Journal of Tourism and Creativity, 2019)
Tourism industry is a sector that is considered potential to be developed in Bondowoso Regency. One of the tourism products developed and a mainstay of the Bondowoso Regency Government is the organic tourism village in Lombok Kulon. However, the limitation of adoption of integrated information technology is the reality in the management of organic tourism village objects. The purpose of this study is to: a). identify the driving and inhibiting factors faced by the manager of the Lombok Kulon organic tourism village to adopt information technology for the development of an organic tourism village, b). formulate a business process design for the development of e-Tourism organic tourism village in Lombok Kulon in accordance with the conditions of supporting resources. This research was conducted by survey method to members and managers of organic tourism villages. The results showed that in the technological aspects, organizational aspects, and environmental aspects provided a strong impetus for technology adoption. This is evident from the recapitulation of the decision to adopt technology. Nevertheless, the inhibiting factor for the adoption of information technology is the assumption of members and managers that the technology to be applied in developing e-Tourism is a technology that is quite difficult.